MiR-133a Mimic Alleviates T1DM-Induced Systolic Dysfunction in Akita: An MRI-Based Study - Nandi, Shyam Sundar; Shahshahan, Hamid Reza; Shang, Quanliang; Kutty, Shelby; Boska, Michael; Mishra, Paras Kumar (Frontiers in Physiology, 2018)
Diastolic dysfunction leading to systolic dysfunction is a hallmark of diabetic cardiomyopathy. However, there is a controversy on whether Akita mouse, a model for T1DM (type 1 diabetes mellitus), shows systolic dysfunction. In the present study, we used magnetic resonance imaging (MRI), a gold standard reference for evaluation of cardiac dysfunction, to determine systolic dysfunction in Akita. In Akita heart, miR-133a, a cardioprotective and the most abundant miRNA in the human heart, is downregulated. Here, we investigated if miR-133a mimic treatment could improve systolic dysfunction in Akita by measuring ejection fraction (EF). To evaluate the anti-hypertrophy and anti-fibrosis effects of miR-133a, we measured cardiac hypertrophy and fibrosis in Akita treated with or without miR-133a mimic. Our results showed ~24% decrease in EF in Akita as compared to WT (EF, WT=60.25±3.96, Akita=46.00±5.83; P=0.06) suggesting systolic dysfunction. However, miR-133a mimic treatment improved EF in Akita (EF, Akita=46.00±5.83, Akita+miR-133a=62.4± 1.89; P=0.02) demonstrating the potential of miR-133a mimic to improve systolic function in Akita. Pathological remodeling in Akita heart was evaluated by determining hypertrophy and fibrosis. We found increased cardiac hypertrophy and fibrosis in Akita, which were decreased by miR-133a mimic treatment. Our findings support systolic dysfunction in Akita and suggest a new potential therapeutic candidate, miR-133a mimic, to mitigate systolic dysfunction and alleviated pathological remodeling in T1DM heart.